Simulation results of the optimum system of vibrations amplitude jumps detection and estimation - Полярус, Олександр Васильович; Барчан, Віталій Володимирович (Eastern-European Journal of Enterprise Technologies, 2010)
The simulation of the optimum system of vibration amplitude jumps detection and estimation is analyzed for dynamic objects.